Inscribing women onto bodies: an encounter with performance, photography and video art from Beijing and Shanghai 1999-2016 - Pittwood, Linda Jean (2019)
Since the turn of the millennium, many contemporary Chinese artists have used their own bodies or actors’ bodies in their performance, photography and video art. These artworks become nodes in the communication of meaning about bodies and gendered categories. This project focuses on how selected objects of contemporary Chinese art represent ‘women.’ The category ‘women’ is understood in this project as not a socially constructed gender or essential sex, but as a role (or roles), practices and attributes linked to gender and sex identity, which can be inscribed onto bodies, including represented bodies. Scholarship at the intersection of contemporary Chinese art and gender has tended to focus on patterns emerging in the outputs and practices of exclusively female-identifying artists. By comparing the outputs of female-identifying and male-identifying artists, this thesis moves forward the debate relating to gendered authorship in international contemporary art and localized contemporary art discourse.